EFFORTS TO INCREASE THE CAPACITY OF RECEPTING GUESTS AND ROOM CLEANING IN STANDARD HOMESTAY BUSINESS IN MANDALIKA TOURISM VILLAGE, CENTRAL LOMBOK - Firman Koma Febdilan (International Journal of Social Science, 2023)
Efforts to increase business standards in the capacity of cleaning rooms and receiving homestay guests are very important things to always improve in serving guests who stay overnight. Lack of facilities and business standards that have been set become the spearhead of the management in services so that guests who stay overnight are satisfied with the services provided. So, in this case the role of the manager is very much needed in understanding this. The purpose of holding this research is to find out how the role of managershomestay Mandalika Tourism Village in providing reception and room cleaning services. Data collection techniques that have been used by the author are observation, interviews, literature studies, and documentation which has been analyzed with interactive communication data analysis models by reducing data, presenting data, and finally drawing conclusions. The results of this study in booking guest rooms, managers still usesystem walk-in and there is no registration form,list room prices and less friendly service to guests. This is evidenced by the lack of association relations or cooperation especiallyonline travel agent to expand the network in the ordering system so that it has an impact on business standardshomestay understanding of managers. This is evident from the product aspect of the availability of at least 1 bedroom with adequate air circulation, ventilation, tiled floors, sufficient lighting, trash cans, room keys, lighting, cupboards, mirrors, beds neatly arranged with other amenities